Incomplete, Slow, and Asymmetric Price Transmission in Ten Product Markets of Bolivia - Varela, Gonzalo J. (World Bank, Washington, DC, 2013)
With food prices on the rise, understanding the transmission of price shocks, both internationally and domestically, is central for trade policy analysis. This paper examines spatial market integration and its determinants for ten key food products in Bolivia, across the four most important cities, and with the world, over the period 1991-2008. Within Bolivia, markets for onions, chicken, sugar, and to a lower extent for potatoes, cooking oil, wheat flour, and rice are integrated. However, only chicken, sugar, cooking oil, and rice are integrated with world markets, with incomplete and slow transmission. The perennial result of asymmetric price adjustment to foreign shocks also holds for Bolivia: domestic prices respond faster when the world price increases than when it decreases. This points to a perennial recommendation: the importance of stimulating competitive practices to avoid welfare redistribution due to imperfect competition. Infrastructure improvements will also contribute to accessible food prices for the poor.